Temporal retinal nerve fibre layer thinning in cluster headache patients detected by optical coherence tomography. (October 2015) - Ewering, Carina; Haşal, Nazmiye; Alten, Florian; Clemens, Christoph R; Eter, Nicole; Oberwahrenbrock, Timm; Kadas, Ella M; Zimmermann, Hanna; Brandt, Alexander U; Osada, Nani; Paul, Friedemann; Marziniak, Martin
Background: The exact pathophysiology of cluster headache (CH) is still not fully clarified. Various studies confirmed changes in ocular blood flow during CH attacks. Furthermore, vasoconstricting medication influences blood supply to the eye. We investigated the retina of CH patients for structural retinal alterations with optical coherence tomography (OCT), and how these changes correlate to headache characteristics, oxygen use and impaired visual function. Methods: Spectral domain OCT of 107 CH patients – 67 episodic, 35 chronic, five former chronic sufferers – were compared to OCT from 65 healthy individuals. Visual function tests with Sloan charts and a substantial ophthalmologic examination were engaged. Results: Reduction of temporal and temporal-inferior retinal nerve fibre layer (RNFL) thickness was found in both eyes for CH patients with a predominant thinning on the headache side in the temporal-inferior area. Chronic CH patients revealed thinning of the macula compared to episodic suffers and healthy individuals. Bilateral thinning of temporal RNFL was also found in users of 100% oxygen compared to non-users and healthy controls. Visual function did not differ between patients and controls. Discussion: Our OCT findings show a systemic effect causing temporal retinal thinning in both eyes of CH patients possibly due to attack-inherent or medication-induced frequent bilateral vessel diameter changes. The temporal retina with its thinly myelinated parvo-cellular axons and its more susceptible vessels for the vasoconstricting influence of oxygen inhalation seems to be predisposed for tissue damage-causing processes related to CH.